Generalizing Fisher's “reproductive value”: Nonlinear, homogeneous, biparental systems - Samuelson, Paul A. (1977)
Biparental demographic models violate linearity. However, in their early “dilute” stages before limited environment resources bring need for competitive selection, first-degree-homogeneous relations obtain. For them, a reproductive-value function of the initial coordinates is defined to recapitulate their contribution to the asymptotically dominating mode of exponential growth: now the generalized Fisher reproductive value of one sex is altered by relative numbers of the other sex. The new reproductive-value function is also derived for general systems of homogeneous-first-degree differential and difference equations, and is shown to grow from the start at the asymptotic growth rate.